A method to predict the torsional resistance of suction caisson with anti-rotation fins in clay. (January 2021) - Fu, Dengfeng; Zhou, Zefeng; Yan, Yue; Pradhan, Dhruba Lal; Hennig, Jørn
Abstract: Suction caisson foundations have been increasingly employed as a primary solution to support the offshore fixed- or mobile-structures. Due to harsh environment and complex force transferring of offshore structures, they are still being developed as to satisfy increasing requirements in strict working scenarios. One of emerging challenges is a torsion-governing failure, which has been observed in the oil and gas industry (i.e. significant multiple-inline-force-induced torsion) and in the renewable energy field (i.e. non-coplanar tensile force induced torsion). This paper introduces a novel suction caisson foundation, with anti-rotational fins assembled on the outer skin of caisson. By a comprehensive numerical study, the evolution from local to global failure as the fin numbers from single to multiple, is examined in the clayey soil deposit with effects of soil strength heterogeneity, fins dimension, installation process and foundation-soil interface considered. Based on these, a set of methods to estimate the ultimate torsional capacity of such novel caisson is proposed, which starts from the gain in capacity for a single fin, and evaluate the changes of gains in capacity as fin numbers, then identify the optimised anti-rotational capacity. Finally, three key parameters (i.e. the required fin numbers, the available anti-rotational capacity and the optimised anti-rotational capacity) with some critical considerations, recommendations and implications have been concluded for design practice. Highlights: This paper introduces a novel suction caisson foundation, with anti-rotation fins assembled on the outer skin of the caisson. By a comprehensive numerical study, evolution of the geotechnical failure mechanism as the fin numbers from single to multiple, is examined in the clayey soil deposit with effects of soil strength heterogeneity, fins dimension, installation process and foundation-soil interface considered. A method is proposed to estimate the ultimate torsional capacity of the novel caisson for design practice. The novel finned suction caisson with remarkable benefits for anti-rotation resistance can be considered as an efficient candidate for offshore energy development.